An Analysis of Creative Thinking Skills among Students of PGSD FIP UNESA - Julianto; Mintohari; Farida Istianah; Suryanti; Supriyono (Universitas Nahdatul Ulama Surabaya, 2022)
Physics is one of the subjects in the science family that emphasizes the development of inductive and deductive analytical thinking skills. Physics can also be used to solve problems related to scientific problems and also develop students' knowledge, skills and perceptions of the scientific world. One of the main aspects that can be developed further is creative thinking skills, which can be categorized as exploratory activities to generate new ideas that are different from existing ones. Therefore, in carrying out classroom learning, students must be actively involved so that their skills can be developed appropriately. The purpose of this study was to determine the level of creative thinking skills and student responses in the PGSD FIP Department. This research is a descriptive research. The population in this study were all students of the 2018-2020 PGSD FIP Department of Unesa with a total sample of 126. All students were taught by researchers, making it easier to collect all the data. The data collection method used in this study was a test. The instrument used in this research is the Creative Thinking Ability Test, which is a written test consisting of five questions in the form of a description, which is used to measure students' creative thinking abilities. This test instrument has been tested and analyzed its items regarding validity, reliability, level of difficulty, and distinguishing power, so it is feasible to be used as a research instrument. In addition, questionnaires were distributed to students to determine students' responses and perceptions of their creative thinking abilities. Closed-type questionnaire was used to provide a clear picture of the perception of students' creative thinking abilities. Based on the results of the data obtained and discussed, it can be concluded that the ability of students' creative thinking skills still needs to be improved even though the responses given by students related to learning that accommodates creative thinking skills that have been carried out in the Department of PGSD FIP Unesa are in the good and very good categories. Therefore, it is necessary to know that it is necessary to take effective steps and approaches to improve students' creative thinking skills in all upcoming learning semesters to ensure that all students in the PGSD FIP Department reach the desired level.